NUTRITIONAL CONTENT OF ANALOG RICE FROM SAGO WITH MUNG BEAN PROTEIN AS A SUBSTITUTE FOR PADDY RICE - mufidah, lina; Mayang Anggraeni, RR. Christiana; Oktaviani, Niken; Rida Tri, Nabilla; Ade Suprana, Yayang (Media Informasi, 2025)
Analog rice is one of the staple food alternatives developed to support national food diversification and reduce dependence on paddy rice. This study aims to analyze the nutritional content of sago-based analog rice and compare it with the nutritional content of white rice (Oryza sativa) in an equivalent portion of 200 grams. Laboratory analysis showed that sago analog rice contains 756 kcal of energy, 174.8 g of carbohydrates, 2.88 g of protein, 5.16 g of fat, and 1.64 g of ash. Meanwhile, in the same quantity, white rice contains approximately 720 kcal of energy, around 156 g of carbohydrates, approximately 13.6 g of protein, and about 1.2 g of fat. The conclusion of this study is that sago analog rice has higher energy and carbohydrate content but significantly lower protein content compared to white rice. Therefore, although sago analog rice has potential as an energy source and utilization of local food resources, reformulation with protein-rich ingredients is necessary to improve its nutritional value. This study supports the development of sago-based analog rice as a strategic food alternative in sago-producing regions, provided that further nutritional enrichment is conducted to make it acceptable as a nutritionally equivalent staple food.